Estudio de las bases bioquímicas y moleculares de la actividad hidrolítica de variantes salvajes y mutacionales de ß-lactamasas CTX-M sobre oximino-cefalosporinas : papel de mutaciones puntuales en la expansión del espectro de hidrólisis - Ghiglione, Bárbara (2015)
Most CTX-M producing microorganisms are usually resistant to cefotaxime but susceptible to ceftazidime. Therefore, these enzymes are called "cefotaximases". However, there are emerging variants possessing the Asp240Gly mutation that are able to confer resistance to cefotaxime and ceftazidime simultaneously.\nIn this work we demonstrate that the Asp240Gly mutation is associated with a ceftazidime resistance phenotype only when Escherichia coli hyperproducing clones lacked porin OmpF in the outer membrane.\nSubstitution of glycine at position 240 does not visibly affect the conformation or the stability of the enzyme, resulting in conserved catalytic efficiencies against most ?-lactam antibiotics. However, the mutation leads to a higher conformational flexibility that allows ceftazidime to accommodate its bulky substituent in the active site cavity, so that it can be hydrolysed more efficiently. CTX-MAsp240Gly ?-lactamases have catalytic efficiencies towards ceftazidime between 5 and 15 times higher than those of their respective wild variants, although these are still at least 200 times lower than cefotaxime.\nDespite having subtle effects on the kinetic behavior, the Asp240Gly mutation can provide a selective advantage when combined with low permeability in a suitable selection environment.\n